2015
DOI: 10.1038/ncomms8588
|View full text |Cite
|
Sign up to set email alerts
|

Allostery through the computational microscope: cAMP activation of a canonical signalling domain

Abstract: Ligand-induced protein allostery plays a central role in modulating cellular signaling pathways. Here, using the conserved cyclic-nucleotide binding domain of protein kinase A’s (PKA) regulatory subunit as a prototype signaling unit, we combine long-timescale, all-atom molecular dynamics simulations with Markov state models to elucidate the conformational ensembles of PKA’s cyclic-nucleotide binding domain A for the cAMP-free (apo) and cAMP-bound states. We find that both systems exhibit shallow free-energy la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
97
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 60 publications
0
97
0
Order By: Relevance
“…We simulated, WT Holo R in five 200ns replicates using the AMBER 17 force field in NTP ensemble at 310K. MD of WT-R Holo reveals a very flexible B/C helix as observed in other simulations 18, 19 . Mutagenesis of B/C helix residues recently showed pronounced effects on PKA activation.…”
mentioning
confidence: 68%
“…We simulated, WT Holo R in five 200ns replicates using the AMBER 17 force field in NTP ensemble at 310K. MD of WT-R Holo reveals a very flexible B/C helix as observed in other simulations 18, 19 . Mutagenesis of B/C helix residues recently showed pronounced effects on PKA activation.…”
mentioning
confidence: 68%
“…3031,69 In these models, microstates are obtained by clustering snapshots according to structural similarity, and transition probabilities between microstates are estimated from molecular dynamics trajectories.…”
Section: Approaches For Characterizing Allosteric Communicationmentioning
confidence: 99%
“…Previous simulation studies have revealed how unidirectional allosteric communication was achieved in Pin1 (19) and sortase A (20). Several simulation studies have already enriched our knowledge on the conformational properties of RIα, including the conformational space sampled by the tandem CBDs in the apo form (21,22) and cAMP-induced conformational changes of the isolated CBD-A (23,24). However, the mechanism of unidirectional allosteric communication between the two cAMP-binding sites has not been addressed and its potential role in PKA deactivation has yet to be explored.…”
mentioning
confidence: 99%